Survival Analysis Statistics Applied to Threshold Data Obtained from the Ascending Forced‐Choice Method of Limits. Issue 5 (16th October 2013) - Hough, Guillermo; Methven, Lisa; Lawless, Harry T.
Abstract Sensory thresholds are often collected through ascending forced‐choice methods. Group thresholds are important for comparing stimuli or populations; yet, the method has two problems. An individual may correctly guess the correct answer at any concentration step and might detect correctly at low concentrations but become adapted or fatigued at higher concentrations. The survival analysis method deals with both issues. Individual sequences of incorrect and correct answers are adjusted, taking into account the group performance at each concentration. The technique reduces the chance probability where there are consecutive correct answers. Adjusted sequences are submitted to survival analysis to determine group thresholds. The technique was applied to an aroma threshold and a taste threshold study. It resulted in group thresholds similar to ASTM or logarithmic regression procedures. Significant differences in taste thresholds between younger and older adults were determined. The approach provides a more robust technique over previous estimation methods. Practical Applications Detection thresholds can indicate the level at which the average person is likely to notice a taste or smell. Therefore, they serve as an informative benchmark of when a tastant or aroma material will have an effect on consumer perception of that taste or flavor. They also serve as an indicator of the biological (sensory) potency of various taste and flavor materials. The survival analysis method outlined in this paper is recommended for the analysis of threshold data collected through the forced‐choice ascending concentration series method of limits. The new method takes into consideration an individual's sequence of incorrect and correct answers and the group's overall performance for a particular concentration, adjusting the individual's answers in a uniform manner. The adjusted answers can then be submitted to survival analysis statistical estimations to obtain more accurate group thresholds.